Does simultaneous adoption of drought-tolerant maize varieties and organic fertiliser affect productivity and welfare outcomes? evidence from rural Nigeria - Oyetunde-Usman, Z.; Shee, A.; Abdoulaye, T. (Australasian Agricultural and Resource Economics Society Inc., 2024)
The promotion of improved maize varieties and chemical fertilisers underscores many policy approaches addressing multiple production risks such as poor soil fertility and drought. However, the unsustainable use of chemical fertilisers has important implications for soil degradation. The synergies between improved maize varieties and sustainable land use management practices such as the use of organic fertilisers (e.g., manure) are poorly documented, despite the role of manure in enhancing soil organic matter. Employing nationally representative household survey data in Nigeria, this study utilises multivalued inverse probability weighted regression adjustment, entropy balancing and a multinomial endogenous switching regression model to determine the effects of the adoption of drought-tolerant maize varieties (DTMVs) and organic fertiliser on farm households' productivity, per capita total expenditure and per capita food expenditure. Controlling for farm households' observables and unobservables, the estimation results of the average treatment effects show that the highest pay-off on productivity and welfare outcomes is achieved when DTMVs and manure are jointly adopted. Also, wealth indicators, access to loans and access to extension services significantly influenced individual and combinatory packages of DTMVs and manure application adoption. This study underlines the significance of the joint adoption of DTMVs and manure application on rural farmers' productivity and welfare and a substantial contribution to achieving sustainable agricultural practices.